Decreased saliva/serum irisin concentrations in the acute myocardial infarction promising for being a new candidate biomarker for diagnosis of this pathology - Aydin, Suna; Aydin, Suleyman; Kobat, Mehmet Ali; Kalayci, Mehmet; Eren, Mehmet Nesimi; Yilmaz, Musa; Baydas, Adil (Elsevier Science Inc, 2014)
Irisin is a muscle-secreted protein. Cardiac muscle produces more irisin than skeletal muscle in response to acute exercise, and is associated with myocardial infarction (MI) in an experimental model induced by isoproterenol in rats. The timing and significance of its release in patients with acute myocardial infarction (AMI) needs further investigation. We have studied the relationship between serum/saliva irisin concentration and AMI in humans. Serum and saliva samples were taken within 3 days of admission in 11 patients with AMI and in 14 matched controls. Salivary gland irisin was detected immunohistochemically, and serum and saliva levels were measured by ELISA. The three major paired salivary glands (submandibular, sublingual and parotid) produce and release irisin into saliva. Troponin-I, CK, CK-MB concentrations in the AMI group gradually increased from up to 12 h, while saliva and serum irisin gradually decreased from up to 48 h, compared with the control group (P < 0.05). After 12 h, troponin-I, CK, CK-MB started to decrease, while saliva and serum irisin started to increase at 72 h. Serum irisin levels correlated with age, while troponin I, CK-MB, and CK were correlated and with saliva irisin in AMI patients. Besides cardiac troponin and CK-MB, irisin adds new diagnostic information in AMI patients, and the gradual decrease of saliva/serum irisin over 48 h could be a useful biomarker. (c) 2014 Elsevier Inc. All rights reserved.
Keywords: Irisin; Myocardial infarction; Saliva; Serum